2001
DOI: 10.1002/1097-4636(2001)58:3<319::aid-jbm1024>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

In vitro andin vivo investigations into the biocompatibility of diamond-like carbon (DLC) coatings for orthopedic applications

Abstract: Diamond-like carbon (DLC) shows great promise as a durable, wear- and corrosion-resistant coating for biomedical implants. The effects of DLC coatings on the musculoskeletal system have not been investigated in detail. In this study, DLC coatings were deposited on polystyrene 24-well tissue culture plates by fast-atom bombardment from a hexane precursor. Two osteoblast-like cell lines were cultured on uncoated and DLC-coated plates for periods of up to 72 h. The effects of DLC coatings on cellular metabolism w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(34 citation statements)
references
References 46 publications
2
32
0
Order By: Relevance
“…Because of its excellent biocompatibility, a-C has been applied to the coatings of hip prostheses, orthopedic implants, vascular stents, and artificial heart valves [13], [20], [21]. A recent study showed that a-C coating on artificial hip joints reduced the wear debris [20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of its excellent biocompatibility, a-C has been applied to the coatings of hip prostheses, orthopedic implants, vascular stents, and artificial heart valves [13], [20], [21]. A recent study showed that a-C coating on artificial hip joints reduced the wear debris [20].…”
Section: Introductionmentioning
confidence: 99%
“…Because of its excellent biocompatibility, a-C has been applied to the coatings of hip prostheses, orthopedic implants, vascular stents, and artificial heart valves [13], [20], [21]. A recent study showed that a-C coating on artificial hip joints reduced the wear debris [20]. Several in vitro studies have also demonstrated that a-C coatings improved the adhesion and growth of osteoblasts, reduced platelet attachment, and inhibited activation [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of the experiment, AAO showed moderate toxicity, while diamond and DLC-AAO were clearly non-toxic—similar to the control experiment on silica (Figure 5). The biocompatibility of DLC-AAO is comparable to diamond, which is acknowledged as a biocompatible material and is used in a variety of medical applications, such as bionic devices and orthopedic implants [17,21,42]. …”
Section: Resultsmentioning
confidence: 99%
“…Diamond related materials are not only used for cell modulation (such as osteoblasts [7], fibroblasts [8], cortical neurons [9], and cortical stem cells [10]), but they also show great promise for biosensing platforms [11,12,13,14,15,16]. Diamond related materials including DLC are used in high-end biomedical applications such as implantable orthopaedic devices, dental and cardiovascular implants and bionic devices [2,17,18,19]. DLC coatings in orthopedic applications reduce wear, corrosion, debris formation and thrombogenicity by minimizing the platelet adhesion and activation [3].…”
Section: Introductionmentioning
confidence: 99%
“…Several experiments with carbon-based biomaterials have already been done, and the biocompatibility of carbon materials has been proven [16, 17]. In addition, CNTs have recently been proven to be safe and effective as biomaterials by cell experiments [18].…”
Section: Introductionmentioning
confidence: 99%